2008
DOI: 10.1089/scd.2007.0181
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Derived from Human Adipose Tissues Favor Tumor Cell Growth in vivo

Abstract: Mesenchymal stem cells (MSCs) have generated a great deal of interest in clinical situations, due principally to their potential use in regenerative medicine and tissue engineering applications. However, the therapeutic application of MSCs remains limited, unless the favorable effects of MSCs for tumor growth in vivo and the long-term safety of the clinical applications of MSCs can be understood more thoroughly. In this study, MSCs derived from human adipose tissues (hASCs) together with tumor cells were trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
2
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(172 citation statements)
references
References 37 publications
9
148
2
8
Order By: Relevance
“…All these factors favor conditions that allow tumorsand might also allow tumor-associated MSCs in our model-to escape immune recognition and foster their proliferation and survival. A number of studies have shown enhancement of tumor growth and development, potentially through immunomodulatory and pro-angiogenic properties of MSCs, whereas others have shown no apparent effect of MSCs or have demonstrated inhibition of tumor growth and extended survival (15)(16)(17). Our results indicate that MSCs have no significant influence on the progression of gliomas in the brain.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…All these factors favor conditions that allow tumorsand might also allow tumor-associated MSCs in our model-to escape immune recognition and foster their proliferation and survival. A number of studies have shown enhancement of tumor growth and development, potentially through immunomodulatory and pro-angiogenic properties of MSCs, whereas others have shown no apparent effect of MSCs or have demonstrated inhibition of tumor growth and extended survival (15)(16)(17). Our results indicate that MSCs have no significant influence on the progression of gliomas in the brain.…”
Section: Discussioncontrasting
confidence: 47%
“…Evidence suggests that MSCs may influence tumor progression in several tumor types (15)(16)(17). To determine the effect of engineered MSCs on glioma growth, we created a human glioma line Gli36-EGFRvIII expressing Fluc-DsRed2 (Gli36-EGFRvIII-FD) by transducing glioma cells with LV-Fluc-Dsred2.…”
Section: Resultsmentioning
confidence: 99%
“…Different MSC classes show tumor cell cytotoxicity, while others do not, which is in consensus with previous reports that proposed contradictory effects of MSCs on tumor cell proliferation [36,59,144]. There is a number of studies that employed cancer cell cultures and a part of them reported intensifying of cancer cell proliferation when MSCs are added [120,121], and some reported recordable MSCs anticancer activity [23,33,34,63,72,144,145]. Conventional anticancer drug screening in vitro is typically performed in the absence of additional cells from the tumor microenvironment, which can alter obtained results about antitumor activity in vivo.…”
Section: New Facts Raised Concerns About Use Of Mscs As An Anticancersupporting
confidence: 85%
“…But the anti-cancer properties of MSCs in humans are controversial because of still incomplete and limited human studies performed on small number of patients. The proposed use of MSCs in cancer therapies provoke strong disagreement in scientific community, due to opposite results for MSC promotion of tumor vascularization, promotion of cancer progression and the invasive tendency of tumors previously reported [28,[120][121][122]. In this contest, Li et al, 2011, inform about the dual role of human MSCs in tumor cell growth in vitro and in vivo.…”
Section: New Facts Raised Concerns About Use Of Mscs As An Anticancermentioning
confidence: 96%
“…In particular, it has to be considered seriously that concerns about the possibility of cancer development derived from cultured autologous adipose stem cells. The reasons for concerns about the possibility of cancer promotion by the administration of cultured adipose stem cells [8,9] are as follows: (1) genetic mutations may occur during the culturing process and (2) the growth factors secreted by stem cells may promote the growth of cancer cells and create a favorable environment for them. However, several reports have presented that stem cells inhibit cancer development [10][11][12], which suggests the importance of discerning the characteristics of cultured stem cells.…”
Section: Introductionmentioning
confidence: 99%